(untitled) (Journal of Dhaka Medical College, 2023)
Introduction: Chronic kidney disease (CKD) is a significant problem that affects all other vital organs and systems. Endocrine dysfunction is not uncommon as well. Early identification of patients with chronic kidney disease (CKD) may help implement interventions to decrease progression and eventual morbidity and mortality. Aim of the study: This study aimed to evaluate the serum testosterone level of adult males with different stages of CKD and its association with body mass index and comparison with agematched healthy individuals. Methods: This cross-sectional study was conducted in the Department of Nephrology, Dhaka Medical College Hospital, Dhaka, Bangladesh. All CKD patients were designated as group ‘A’ with 90 cases; the healthy control group were grouped as group ‘B’ with 88 cases. Result: In this study, the majority 40(44.4%) of patients had glomerulonephritis, 24(26.8%) had DM and 11(12.2%) had HTN. The mean BMI was found to be 20.85±2.7 kg/m2. More than two-thirds (66.7%) of patients had normal (3.2-14.6 ng/ml) Serum testosterone, and their mean Serum testosterone was found at 4.29±1.9 ng/ml. Negative Spearman’s rank correlation (r=- 0.893; p=0.001) was observed between different stages of CKD and S. Testosterone of CKD patients. A positive Pearson correlation existed (r=0.517; p=0.001) between BMI and S. Testosterone of CKD patients. Conclusion: A significant positive correlation existed between BMI and serum testosterone of CKD patients. J Dhaka Med Coll. 2022; 31(1) : 66-70